2003
DOI: 10.1088/0957-4484/14/9/318
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale synthesis of arrays of high-aspect-ratio rigid vertically aligned carbon nanofibres

Abstract: We report on techniques for catalytic synthesis of rigid, high-aspect-ratio, vertically aligned carbon nanofibres by dc plasma enhanced chemical vapour deposition that are tailored for applications that require arrays of individual fibres that feature long fibre lengths (up to 20 µm) such as scanning probe microscopy, penetrant cell and tissue probing arrays and mechanical insertion approaches for gene delivery to cell cultures. We demonstrate that the definition of catalyst nanoparticles is the critical step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 25 publications
4
60
0
Order By: Relevance
“…Energy-Dispersive-X-ray (EDX) analysis performed by Melechko et al, has indicated the presence of a sheath of SiNx on the CNF sidewalls for tubes synthesized on Si. 26 The presence of such a dielectric coating on the sidewalls of the CNFs grown on Si would explain the data we obtained in curve 3 of Fig. 7.…”
Section: Electrical Actuation In Vertically Oriented Carbon Nanofiberssupporting
confidence: 51%
“…Energy-Dispersive-X-ray (EDX) analysis performed by Melechko et al, has indicated the presence of a sheath of SiNx on the CNF sidewalls for tubes synthesized on Si. 26 The presence of such a dielectric coating on the sidewalls of the CNFs grown on Si would explain the data we obtained in curve 3 of Fig. 7.…”
Section: Electrical Actuation In Vertically Oriented Carbon Nanofiberssupporting
confidence: 51%
“…II C 3 and ͑2͒ compounds of redeposited substrate material, for instance silicon, which can react with the nitrogen from the ammonia etchant gas to form Si x N y coatings on the surface. 66,70,89 The sidewall deposition of carbon films was first reported by Chen et al in a high temperature, high pressure, hot filament PECVD process. 87 They observed formation of conical structures, shown in Fig.…”
Section: In Situ Pecvd Coatings and Surface Modificationmentioning
confidence: 99%
“…While further work is necessary to investigate the effects of other growth parameters, it is clear that growths conducted at higher initial currents can be used to synthesize essentially defect-free single row barriers and ordered nanofiber arrays with reasonable yields. The taper, or conical nature of the fibers, results from sidewall deposition of silicon nitride during the deposition process as discussed by Melechko et al [7] In Fig. 5, an ordered fiber array is shown next to a random nanofiber forest, contrasting the difference in density and consistency of morphology of fibers grown from catalyst particles resulting from discrete patterning (ordered array) and the break-up of a catalyst thin film (random forest).…”
Section: Resultsmentioning
confidence: 93%
“…The impact of pressure, temperature, gas ratio, choice of catalyst material, and even catalyst geometry on fiber morphology and growth rate have been explored [7][8][9][10][11][12][13][14][15][16]. Furthermore, the integration of ensembles of individual fibers and stochastic nanofiber forests into functional devices for electrochemical and biochemical sensing [17][18][19][20][21][22][23][24][25][26], gated-cathode field emitters [27][28][29], barriers to material transport [30][31][32] and templates for the synthesis of nanofluidic nozzles, or nanopipes [33,34], has also been described.…”
Section: Introductionmentioning
confidence: 99%